Diseño y construcción de un colector secador solar para quinua y amaranto aplicado al proyecto de granos andinos en la facultad caren en la universidad técnica de Cotopaxi. - Alvarez Amores, Stalin Fabián (2019)
The objective of the present project was to design, build and implement a Quinoa and Amaranth solar dryer collector and thus improve the drying process and storage quality of these products, to be subsequently planted or experienced in the Andean grains laboratory from the Technical University of Cotopaxi in its Salache campus. In the design of the dryer, a previous investigation was carried out to determine the ideal parameters, adapted to the working condition and quantity of the material to be dried. In the foreground, the theoretical framework is detailed, where solar drying technologies were investigated, as well as the types of dryers.In the second instance the methodology for the design is observed, where the most basic formulas for the design the solar dryer were taken into consideration, by means of the analysis the norms corresponding to the construction of this system, with which it was determined that a drying chamber has similar characteristics to those of an oven, in this sense it was decided to acquire a four-tray oven, which covers 1kg per tray, so the design the trays, was only similar in terms of measurements, with the variant that a 60 micron mesh was acquired so the flow of hot air through the grain circulates freely.At the request of the beneficiary it was necessary to implement an auxiliary electrical system, which guarantees a continuous flow of heat, which works with a temperature controller when the climatic conditions of the site are not favorable. The drying process will continue through the mentioned system.After the tests were performed, it was observed that it fulfilled the requested needs since the samples of 500g of Quinoa and 200g of Amaranth were dried in an average of 4 hours, until reaching its standards of 9% and 11% respectively, these standards were determined through the use of a precision balance and a humidity meter, taking data in half an hour, so that the expected expectations were met.